2016
DOI: 10.1016/j.electacta.2016.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Insight into CO Activation over Cu(100) under Electrochemical Conditions

Abstract: Sun, Insight into CO Activation over Cu(100) under Electrochemical Conditions, Electrochimica Acta http://dx.doi.org/10. 1016/j.electacta.2016.01.037 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 58 publications
(75 reference statements)
1
19
0
Order By: Relevance
“…From our previous calculation, one can see that the corresponding electrode potential in neutral system (potential of zero charge) is -0.63 (vs SHE), comparing with the experimental value of -0.54 V (vs SHE). 25 For the charged interface model including H + , the corresponding electrode potential is -2.04 V (vs SHE), more negative than the onset potential of -1.4 V (vs SHE) in CO 2 electroreduction on Cu(100). 8 Using the water/Cu(100) interface and the charged water/Cu(100) interface can help to decouple the effects of aqueous surrounding and electrode potential for investigating them respectively.…”
Section: Computational Detailsmentioning
confidence: 99%
See 4 more Smart Citations
“…From our previous calculation, one can see that the corresponding electrode potential in neutral system (potential of zero charge) is -0.63 (vs SHE), comparing with the experimental value of -0.54 V (vs SHE). 25 For the charged interface model including H + , the corresponding electrode potential is -2.04 V (vs SHE), more negative than the onset potential of -1.4 V (vs SHE) in CO 2 electroreduction on Cu(100). 8 Using the water/Cu(100) interface and the charged water/Cu(100) interface can help to decouple the effects of aqueous surrounding and electrode potential for investigating them respectively.…”
Section: Computational Detailsmentioning
confidence: 99%
“…23, 24 We previously revealed that adsorbed COH was favorable kinetically but CHO was favorable thermodynamically in CO activation on Cu(100). 25 In fact, the mechanism to explain how copper catalyzes CO 2 to hydrocarbons still remains controversial and requires further studies. Hori et al carried out the CO 2 electroreduction over a series of Cu single crystal planes, it was found that the activity on Cu(100) and Cu(111) single crystal surfaces is comparable, e.g., a current density of 5 mA cm -2 was achieved at a reduction potential of -1.4 V (vs SHE) on Cu(100) and -1.5 V (vs SHE) on Cu(111), respectively.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations